REGIONAL INTEGRATION IN AFRICA: THE CASE OF CENTRAL AFRICA (analysis of processes, issues and constraints) - (:unkn) unknown (My University, 2018)
In Central Africa, state and transnational actors structure regional integration processes through their behavior. On the one hand, Central Africa presents itself as a complex of institutions of regional integration with variable realities and geometry, whose state actors contribute to their creation, structuring, restructuring and functioning. On the other hand, the transnational dynamics of regional integration stems from the transcendence of international borders by frontier peoples, from the perpetuation of their community consciousness, and finally from the double movement of appropriation and internalization of the aspirations of peoples by state actors. These processes of integration structure the identities and interests of the actors. However, their games are structured by several intrinsic and extrinsic constraints that partially compromise the effectiveness of their actions and interactions. These include the multi-positionality of states, institutional overlap, inadequate channels of communication, selfish national interest, political instability of states, inadequate funding and recruitment mechanisms of human resources, organized cross-border crime, the troubled game of financial partners and exogenous shocks. In order to place this region at the center of global issues, the analysis proposes the transcendence of these constraints. It invites osmosis between the aspirations of the peoples and the state initiatives in order to reinforce the acquired identities, the tangibility of the structures and the feeling of belonging to the same community of destiny, giving rise at the same time to a real integration of the peoples institutionalized by state actors. It also suggests innovative financing mechanisms, strengthening of the peace and security arrangements, development of channels of communication, the criterion of competence in recruiting human resources, good governance, diversification of state economies and rationalization of structure
Keywords: African Research